IMPLEMENTASI PROGRAM PENGEMBANGAN DESA PESISIR TANGGUH (PDPT) TAHUN 2012-2014 DI KABUPATEN KENDAL - Andi Bayu Mukti Wicaksono; Muhammad Adnan; Lusia Astrika (Journal of Politic and Government Studies, 2015)
AbstractKendal is a regency with a wide coastal and marine area. However, the coastal communities in Kendal are usually being excluded and did not get any attention from the government. The quality of environmental, infrastructure and income of the people in the coastal village of Kendal is quite low. It surely needs such an attention by the government, because it accounts for a high poverty rate in this area. This problems are eventually got the attention of the Ministry of Maritime Affairs and Fisheries. MMAF had develop the Resilient Coastal Rural Development program (PDPT). The purpose of this program are to reorganize and improve the village life. This program is focused on the developing the human resource, infrastructure of coastal areas and supporting the development of productive economic business climate.In order to reveal the problems and the purposes of the study, researchers uses a qualitative descriptive approach. In analyzing the data, the researcher used the descriptive-qualitative. The purpose of the study is to find out how the implementation of the Rural Development Program of the Resilient Coastal is applied in Kendal. The data obtained is used to formulate a recommendation as a form of suggestion for the sustainability of coastal development in Kendal.The result showed that in order to develop the coastal areas in Kendal, local governments should encourage the participation of the community to participate in the development process. It means that the community itself that should carry out activities, starting from planning, implementing until the monitoring. Based on the research, the implementation of PDPT program was considered as good enough, refers to the variable of the implementation of the program. The purpose of this program have been accomplished, it can be seen from the improvements in the quality of infrastructure, rural financial independence through BUM-Des and the creation of productive business climate in the coastal village. However, there are shortcomings in its implementation namely the purpose of the programs which related to the group empowerment that shifted to the individual empowerment. It is characterized by the dissolution of most Coastal Communities Group (KMP) organizations after the program ends.The recommendations that can be given are: the preparation must be done thoroughly before the program is actually applied, so that the community could understand about the technical implementation of the program. In addition, it needs such a seriousness and commitment of all parties to develop the coastal villages, so that the implementation will not only be considered to accomplish such a budget absorption target. Keywords: Program Implementation, Resilient Coastal Village Development